Home Sanitation and Nutritional Status as Risk Factors of Pulmonary Tuberculosis (TB) at Karang Taliwang Health Centre, Mataram, West Nusa Tenggara - Lisa Sutiasih; Dewa Nyoman Wirawan; Anak Agung Sagung Sawitri (Universitas Udayana, 2014)
Background and purpose: Tuberculosis (TB) is a continuing health problem in Mataram, particularly at the Karang Taliwang Health Centre (KTHC), which has the highest prevalence of TB - 294/100,000 in 2010; 173/100,000 in 2011. This study investigates the risk factors of pulmonary TB in KTHC. Methods: Study design used was a case control, 46 respondents with pulmonary TB and 92 persons without either TB/acute respiratory infection were controls. Variables examined were: house sanitation, socio-economic, nutrition, cigarette smoke exposure, other infections and immunisation status. Data was obtained by direct survey on site, measurement using role meter, hygrometer, lux-meter, mistar and HIV test. Data were analysed using univariate, bivariate and multivariate analysis. Results: Bivariate analysis shows that risk factors were house sanitation (ventilation, humidity, light and population density), socio-economic factors, nutritional status and other disease. Multivariate analysis indicated risk factors were: ventilation with OR=2.87 (95%CI: 1.01-8.20), humidity with OR=3.91 (95%CI: 1.28-11.89), sunlight access with OR=4.46 (95%CI: 1.34-14.85), temperature with OR=5.41 (95%CI: 1.90-15.39), nutrition with OR=6.74 (95%CI: 2.52-18.02). These factors contributed to 48.9% TB occurences. Conclusion: This study found that house sanitation and nutritional status are risk factors of of TB transmission at KTHC, Mataram.